Melatonin protects against lipid‐induced mitochondrial dysfunction in hepatocytes and inhibits stellate cell activation during hepatic fibrosis in mice. Issue 4 (27th March 2017) - Das, Nabanita; Mandala, Ashok; Naaz, Shamreen; Giri, Suresh; Jain, Mukul; Bandyopadhyay, Debasish; Reiter, Russel J.; Roy, Sib Sankar
Abstract: Lipid generates reactive oxygen species (ROS) in consequence to mitochondrial fission followed by inflammation in propagating hepatic fibrosis. The interaction of SIRT1/Mitofusin2 is critical for maintaining mitochondrial integrity and functioning, which is disrupted upon excess lipid infiltration during the progression of steatohepatitis. The complex interplay between hepatic stellate cells and steatotic hepatocytes is critically regulated by extracellular factors including increased circulating free fatty acids during fibrogenesis. Melatonin, a potent antioxidant, protects against lipid‐mediated mitochondrial ROS generation. Lipotoxicity induces disruption of SIRT1 and Mitofusin2 interaction leading to mitochondrial morphological disintegration in hepatocytes. Further, fragmented mitochondria leads to mitochondrial permeability transition pore opening, cell cycle arrest and apoptosis and melatonin protects against all these lipotoxicity‐mediated dysfunctions. These impaired mitochondrial dynamics also enhances the cellular glycolytic flux and reduces mitochondrial oxygen consumption rate that potentiates ROS production. High glycolytic flux generates metabolically unfavorable milieu in hepatocytes leading to inflammation, which is abrogated by melatonin. The melatonin‐mediated protection against mitochondrial dysfunction was also observed in high‐fat diet (HFD)‐fed mice through restoration of enzymatic activities associated with respiratory chain and TCA cycle. Subsequently, melatonin reduces hepatic fat deposition and inflammation in HFD‐fed mice. Thus,  melatonin disrupts the interaction between steatotic hepatocyte and stellate cells, leading to the activation of the latter to abrogate collagen deposition. Altogether, the results of the current study document that the pharmacological intervention with low dose of melatonin could abrogate lipotoxicity‐mediated hepatic stellate cell activation and prevent the fibrosis progression.